THE ROLE OF THE ASEAN SUMMIT IN THE ASEAN ECONOMIC DISPUTE SETTLEMENT - Intan Soeparna (JAS (Journal of ASEAN Studies), 2021)
Like the World Trade Organization (WTO) Dispute Settlement Mechanism, the Association of South-East Asian Nations Enhanced Dispute Settlement Mechanism (ASEAN EDSM) recognizes trade countermeasures in the event of non-compliance with rulings made by the Panel and Appellate Body. However, the injured party sometimes has to deal with stumbling blocks in requesting an authorized trade countermeasure. The pitfall highlights the consequences if the dispute is unresolved. Meanwhile, ASEAN recognizes a procedure to allow the disputant parties to render unresolved disputes to the ASEAN Summit according to Article 26 of the ASEAN Charter. Moreover, if the non-implementation of the ASEAN dispute settlement decision affects the injured party, this party can submit the issue to the ASEAN Summit according to Article 27(2) of the ASEAN Charter. This research investigates whether the role of the ASEAN Summit can be a solution for the post-adjudication issue in the ASEAN EDSM. The research methods consist of a literature review and close reading of the Article 26 and 27 of the ASEAN Charter. The result shows that the intervention of the ASEAN Summit to the post-adjudication of ASEAN EDSM is likely to apply political solutions that would, in turn, make legal decisions subject to politically driven scrutiny. However, ASEAN commits that any economic disputes must be resolved to ensure economic stability in the ASEAN.